2015
DOI: 10.3892/ol.2015.3057
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor mutation heterogeneity analysis of pulmonary sarcomatoid carcinoma successfully treated with erlotinib: A case report

Abstract: Abstract. Pulmonary sarcomatoid carcinoma (PSC) is a rare histological subtype of non-small cell lung cancer, and the available studies on the response to epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) is limited. In the present study, a 73-year-old female presented with a large mass in the lower right lung, which was diagnosed as a PSC on biopsy. An amplification-refractory mutation system (ARMS) test revealed that the patient possessed the wild-type EGFR gene, and the patient subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
(11 reference statements)
0
20
0
Order By: Relevance
“…[10][11][12][13][14] However, recent studies have identified targetable hepatocyte growth factor receptor gene (MET) exon 14 skipping and KRAS alterations in a significant fraction of cases. 12,15,16 Isolated reports of responses to targeted therapy have been presented, 15,17,18 but PSC remains a tumor type with little demonstrated efficacy of any targeted therapy in the clinic. Herein, we present results of comprehensive genomic profiling (CGP) of the largest series to date of patients with PSC, including patients with diverse genomic alterations (GAs) experiencing clinical benefit to targeted therapies and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] However, recent studies have identified targetable hepatocyte growth factor receptor gene (MET) exon 14 skipping and KRAS alterations in a significant fraction of cases. 12,15,16 Isolated reports of responses to targeted therapy have been presented, 15,17,18 but PSC remains a tumor type with little demonstrated efficacy of any targeted therapy in the clinic. Herein, we present results of comprehensive genomic profiling (CGP) of the largest series to date of patients with PSC, including patients with diverse genomic alterations (GAs) experiencing clinical benefit to targeted therapies and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…KRAS mutation has been reported in up to 38% of PSCs and EGFR mutations in up to 25% . Furthermore, few recent studies have identified targetable MET exon 14 skipping in a significant fraction of cases, with a few case reports demonstrating a great response to targeted therapy with MET inhibitors . Despite these advancements, there are still limited options available for treatment of these tumours.…”
Section: Introductionmentioning
confidence: 99%
“…6,[8][9][10] Furthermore, few recent studies have identified targetable MET exon 14 skipping in a significant fraction of cases, 3,7,9 with a few case reports demonstrating a great response to targeted therapy with MET inhibitors. 11,12 Despite these advancements, there are still limited options available for treatment of these tumours. In addition, there are no clinicopathological or molecular features that could predict outcome reliably in PSC patients.…”
Section: Introductionmentioning
confidence: 99%
“…First-line chemotherapy drugs for NSCLC include platinum, such as cisplatin and carboplatin, while platinum resistance often leads to chemotherapy failure [ 13 , 14 ]. Platinum drugs can combine with nucleophilic DNA in tumor cells to form DNA-platinum adduct, thus inhibiting DNA replication, causing DNA damage, and ultimately inducing tumor cell death [ 15 ]. However, the DNA damage repair system can modify DNA damage to various extents, which affects the sensitivity of chemotherapy drugs.…”
Section: Discussionmentioning
confidence: 99%